Transparency, Recruitment and Retention in the Public Sector. - Albano, G; Leaver, C (Department of Economics (University of Oxford), 2004)
This paper argues that governments should pay greater heed to recruitment and retention when designing performance measurement systems for bureaucracies. In the face of pervasive rigidities in public sector pay, internal performance measurement rewards quitters and scars stayers and therefore makes it difficult to recruit and retain. Full and immediate publication of performance minimizes the cost of initial recruitment but entails retaining and paying rents to poor performers. This is optimal only if skill differences are low and the value of public production is moderate: high enough to warrant recruitment but not so high that good performers are retained. Human capital objectives are typically better met by abstaining from performance measurement altogether or ‘stage-managing’ its publication, suggesting that the current emphasis on incentives and accountability may be misplaced.